2018
DOI: 10.1152/ajpregu.00193.2017
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of antenatal steroids

Abstract: Antenatal steroids (ANS) are among the most important and widely utilized interventions to improve outcomes for preterm infants. A significant body of evidence demonstrates improved outcomes in preterm infants (24-34 wk) delivered between 1 and 7 days after the administration of a single course of ANS. Moreover, ANS have the advantage of being widely available, low cost, and easily administered via maternal intramuscular injection. The use of ANS to mature the fetal lung is, however, not without contention. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 111 publications
(134 reference statements)
0
24
0
Order By: Relevance
“…ACS reduce the risk of serious adverse prematurityassociated outcomes including neonatal death, respiratory distress syndrome and severe intraventricular haemorrhage 6,7 . Despite being used clinically for nearly 50 years, dosing to optimize benefit remains largely unexplored 6,[8][9][10] . A goal for ACS should be to minimize fetal exposure to decrease the potential for long term adverse effects such as growth restriction 11,12 , reduced academic ability 13 , elevated stress responses 14 , altered insulin responsiveness in the adult 15 , and possible epigenetic/ transgenerational effects 16 Using maternal infusions and the maternal intramuscular delayed release (acetate) form of betamethasone, we previously demonstrated in a sheep model that a low fetal plasma exposure in the range of 1-4 ng/mL betamethasone for 26 hours was sufficient to induce lung maturation at 2 days 17,18 .…”
Section: [Abstract]mentioning
confidence: 99%
“…ACS reduce the risk of serious adverse prematurityassociated outcomes including neonatal death, respiratory distress syndrome and severe intraventricular haemorrhage 6,7 . Despite being used clinically for nearly 50 years, dosing to optimize benefit remains largely unexplored 6,[8][9][10] . A goal for ACS should be to minimize fetal exposure to decrease the potential for long term adverse effects such as growth restriction 11,12 , reduced academic ability 13 , elevated stress responses 14 , altered insulin responsiveness in the adult 15 , and possible epigenetic/ transgenerational effects 16 Using maternal infusions and the maternal intramuscular delayed release (acetate) form of betamethasone, we previously demonstrated in a sheep model that a low fetal plasma exposure in the range of 1-4 ng/mL betamethasone for 26 hours was sufficient to induce lung maturation at 2 days 17,18 .…”
Section: [Abstract]mentioning
confidence: 99%
“…A large experimental literature in animal models from rodents to primates has shown adverse developmental, behavioral, and transgenerational effects of ACS. 10 ACS decrease birth weight by a small amount and may increase the risk of hypoglycemia in late preterm infants. 9 A significant concern with fetal exposure to ACS is the potential for adverse cardiovascular and metabolic effects in later life.…”
Section: What Is the Optimal Antenatal Corticosteroid Treatment?mentioning
confidence: 99%
“…Since Liggins' original work with corticosteroid infusions in sheep, researchers have utilized multiple animal models to verify the maturational effects of ACS, including rodents, sheep, and primates. 10 Liggins and Howie demonstrated that a continuous fetal exposure of corticosteroids induced lung maturation. 5 However, clinical dosing with betamethasone phosphate (including as a combined preparation of betamethasone phosphate and acetate) or dexamethasone phosphate results in high early maternal blood levels because the drugs are rapidly dephosphorylated to betamethasone or dexamethasone, respectively, which in turn cross the placenta to expose the fetus to high peak drug levels that then decrease over hours to low levels.…”
Section: Corticosteroid Treatment For Lung Maturation -Sheepmentioning
confidence: 99%
“…A great deal is known about the maturational effects that endogenous as well as exogenous glucocorticoids have on the lungs (Bird et al 2015, Roberts et al 2017). However, the role of glucocorticoids in the maturation of other fetal organs has not been well characterised and concerns have been raised that non-optimal antental glucocorticoid therapy might increase adverse outcomes, including perinatal death (reviewed in Kemp et al 2018). The effects of endogenous glucocorticoids upon fetal heart maturation were, until recently, unclear.…”
Section: Introductionmentioning
confidence: 99%